Shaping the Communal Past, Tinkering with the Communal Past. A Few Notes in the Margin of Piotr Okniński’s Book - Adamska, Anna (1964– ) (Fundacja Instytutu Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
The article discusses a thought-provoking – though not entirely unproblematic – attempt to investigate attitudes towards the past in the urban context of premodern Poland. The work in question, Piotr Okniński’s monograph on the creation of official historical narratives of the city of Kraków, is examined against the broader backdrop of both Polish and international scholarly discourse. This discourse concerns the mechanisms of collective memory and its politically motivated suppression, the instruments of remembrance, and the active role of urban elites in shaping an authorised version of the communal past.
Concerns book : Wehikuły pamięci : przeszłość i władza w dawnym Krakowie : (do końca XVIII w.) / Piotr Okniński. - Warszawa : Wydawnictwa Uniwersytetu Warszawskiego, 2023.
p. 203-213
Keywords: pre-modern Kraków; urban elites; urban chanceries; collective memory; communal past